Cλ -semiconservative FK-spaces - Dağadur, I. (Український математичний журнал, 2012)
We study Cλ -semiconservative FK-spaces for Cλ -methods defined by deleting a set of rows in the Cesáro matrix C₁ and give some characterizations. Вивчено Cλ-напiвконсервативнi FK-простори для Cλ-методiв, що визначаються видаленням групи рядкiв iз матрицi Чезаро C₁, i наведено деякi характеристики.